Thermotolerant insect-associated selective pressure may drive increased lipid metabolic plasticity and emerging pathogenic potential in yeasts - Van Baalen, Casey; Zhou, Nerve; Boekhout, Teun; Sebolai, Olihile M.; Albertyn, Jacobus; Pohl, Carolina H. (Frontiers in Microbiology, 2026)
The emergence of pathogenic yeasts such as Candidozyma auris represents a growing global health threat. Despite advances in fungal genomics, the ecological and physiological origins of pathogenicity in yeasts remain poorly understood. Most yeasts thrive at mesophilic temperatures, with a sharp decline in biodiversity beyond 30 °C, limiting the ability of many yeasts to infect endothermic hosts. Most insects, as ectothermic organisms with variable and often elevated body temperatures, co-exist intimately with yeasts in diverse environments and exert unique selective pressures, particularly regarding thermal stress. We hypothesise that these interactions potentially select for yeasts with enhanced lipid metabolic plasticity, a key trait underlying thermotolerance, immune evasion, nutrient adaptation, and antifungal resistance—attributes central to fungal virulence and pathogenicity and that thermotolerant insects thus act as ecological bridge for yeasts to move between the environment and endothermic hosts.